Slovenia Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2016)
This assessment of accounting and auditing practices in Slovenia is part of a joint initiative of the World Bank and International Monetary Fund (IMF) to prepare Reports on the Observance of Standards and Codes (ROSC). The assessment focuses on the strengths and weaknesses of the accounting and auditing environment that influence the quality of corporate financial reporting and includes a review of both mandatory requirements and actual practice. This is the second A&A ROSC for Slovenia and based on information collected in 2013, early 2014. The first one was published in 2004. As the requirements of the EU acquis communautaire and international standards have already been adopted in the financial sector this assessment focuses on the proper application of these requirements, with the view that improved financial information raises the capacity of regulators to maintain financial stability, and improve the level of trust in the financial system, in the context of an ongoing recapitalization exercise. In the State Owned Enterprises, or SOEs, the report focuses on the requirements applicable to them and how well these are enforced, as well as to what extent the government uses the financial reporting and audit process to monitor SOEs and hold their management teams accountable. This report also considers SMEs financial reporting, including how current requirements compare with the latest revisions to the EU Accounting Directive, which further simplified requirements for smaller companies. Finally, audit oversight and quality assurance systems are assessed, including the feasibility of incorporating the audit oversight body as part of the financial sector supervisor.